Hepatoprotective Effect of Black Garlic Extract against Carbon Tetrachloride Induced Liver Injury in Rats - Abdul Ghaffar Ansari, Aftab Ahmed Shaikh, Zaheer Ahmed Memon , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
o investigate the protective effect of Black Garlic extract (BGE) in carbon tetrachloride (CC14) induced liver injury in adult male Wistar rat model. Study design: Experimental /Analytical study Place and Duration: Animal House, Isra University Hyderabad from May to September 2013. Material & Methods: Sixty adult male Wistar rats were divided into three groups; Group I controls received 0.9% isotonic saline, Group II received CC14 orally (1.9mg/kg) mixed in olive oil, and Group III. received the BGE (100 mg/kg) + CC14. After 4 weeks blood samples of animals were collected for liver biochemical assays. The animals were sacrificed, liver tissue, after fixation in 10% formaldehyde, was embedded in paraffin. Tissue sections of 5p. thickness were subjected to haematoxylin and eosin staining and were assessed by light microscopy. The data was analyzed on Statistix 8.1 (USA) using one-way ANOVA, Bonferroni and Chi-square tests. P-value of =0.05 was taken statistically significant. Results: The biochemical and histological findings of liver showed statistically significant differences between the controls, CC14 and BGE+CC14 groups (p=0.001). Liver enzymes and histology was deranged significantly in CC14 group compared to controls and BGE+CC14 group (p=0.001). The BGE+CC14 group showed less rise of liver enzymes and derangement of liver histology when compared to CC14 group (p=0.001). The histological findings of congestion, inflammatory cell infiltrate, vacuolar degeneration and necrosis were prominently found in CC14 group. Conclusion: The Black Garlic extract (BGE) protects against oxidative damages caused by carbon tetrachloride induced liver injury in rat model.